Drug Utilization Evaluation of Anticancer Drugs in a Tertiary Care Teaching Hospital: a Descriptive Observational Study - Vinodkumar Mugada, Aswinichand Paruchuri, Mounika Munagala (Journal of Applied Pharmaceutical Science, 2016)
Drug Utilization Evaluation (DUE) promotes rational use of drugs. The aim of present study was to conduct DUE of anticancer drugs. Newly diagnosed and/or known case of carcinoma which required treatment with chemotherapy, patients of both sex, and age >18 years were included in the study. Patients diagnosed as having carcinoma that also required surgical intervention, radiotherapy or other modality of management were excluded from the study. WHO core prescribing indicators are used to know about polypharmacy, excessive use of antibiotics, percentage of drugs prescribed by from Essential Drugs List (EDL). Females were commonly affected than males. Patients of age group 41-50 years (mean 52.43, SD ±7.77) constituted the highest number, 34% and 13% in rural and urban population respectively. 5-Flurouracil and Cisplatin are most commonly prescribed anticancer drugs followed by Cyclophosphamide. The most commonly used adjuvant drugs in our study are Diclofenac, B-Complex, Granisetron, Ranitidine, Dexamethasone, Ondansetron, and Mannitol. The cytoprotectant drugs observed in our study are Leucovorin, Mesna and Peg-Filgrastim. Average number of Cytotoxic Drugs per prescription was 1.97. Average number of drugs per prescription was 8.16. Percentage of drugs prescribed from Essential Drugs List (EDL) was 88.4%. Percentage of encounters with an antibiotic prescribed was 54.8%. Polypharmacy, unnecessary antibiotic and injection prescribing were not observed. The percentage of drugs from EDL may be improved.
Keywords: Drug Utlization Evaluation, Essential Drugs List, WHO core prescribing indicators, polypharmacy, rational.